Sudan : Midyear Review of the 2005 Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2005)
This paper on the midyear review of the 2005 staff-monitored program for Sudan reports that after a mixed performance under the staff-monitored program, the authorities are taking corrective measures to bring the program back on track. They imposed strict controls on nonpriority government spending, tightened monetary policy, and committed to stop nonconcessional borrowing. Expenditures should be allocated to priority sectors and high-return projects, and fuel subsidies should be reduced. The oil saving account will continue to play an important role in providing self-insurance against an oil price shock.